Correlates of Objectively Measured Physical Activity Among People With Multiple Sclerosis: A Cross-Sectional Study - Fortune, Jennifer; Norris, Meriel; Stennett, Andrea; Kilbride, Cherry; Lavelle, Grace; Hendrie, Wendy; DeSouza, Lorraine; Victor, Christina; Ryan, Jennifer Mary (Frontiers in Rehabilitation Sciences, 2021)
Background: Identifying correlates of physical activity (PA) for people with multiple sclerosis (MS) is essential to design effective PA interventions. Methods: Participants completed a battery of questionnaires and wore an ActiGraph accelerometer. Light physical activity (LPA) and moderate-to-vigorous physical activity (MVPA) (min/day) were calculated. Associations were examined using multiple linear regression adjusted for demographic and clinical confounders. Results: Fifty-eight adults with MS participated (mean ± SD age: 56.8 ± 9.2 yr; 67% women). MS type was associated with time in LPA. Participants with secondary progressive MS (B = −54.0, 95% CI −84.7 to −23.3) and primary progressive MS (B = −42.9, 95% CI −77.5 to −8.3) spent less time in LPA than those with relapsing remitting MS. Walking capacity, assessed using the 12-item MS walking scale (MSWS-12), was associated with time in MVPA (B = −0.36, 95% CI −0.72 to −0.01). Conclusion: This work identifies walking capacity and type of MS as correlates of PA, which may indicate development of interventions to promote PA.